Pengabdian Masyarakat: Penggunaan Platform Socrative Sebagai Media Pembelajaran dan Penilaian Digital yang Efektif - Fredy Meyer; Yulina Tiwery (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This community service activity (PKM) aims to improve the ability of teachers and students at SMP, SMA, and SMK in Negeri Weet to use the socrative platform or application as a medium for digital learning and assessment. The method used in this activity is the service learning method, which is divided into material presentation, interactive discussions, simulations, and training on using the Socrative application. In using this application in the classroom, teachers can provide quizzes directly to students, as it can be accessed using computers or students' mobile phones. This application not only helps students learn but also makes it easier for teachers to provide assessments. Using this application in the classroom also provides benefits, such as building good interactions between teachers, students, and classmates. This is supported by several features that facilitate teachers and students, including quick questions, space race, and exit ticket, polling, and discussion. Thus, activities in the learning space become more lively and enjoyable. This PKM activity involved 23 participants, consisting of 7 teachers and 16 students representing the three schools. The results of the activity show that teachers and students were very enthusiastic and active in following the material presentation sessions, discussions, simulations, and training. This activity had a positive impact on improving teachers' and students' abilities in using digital learning technology and assessment.